2023
DOI: 10.1515/pz-2022-2045
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of chemical composition of cribra orbitalia from post-medieval children graves (Olomouc, Czech Republic)

Abstract: During an archaeological rescue excavation in center of city Olomouc (Moravia region, Czech Republic) several graves were found. Those graves were a part of a defunct cemetery situated in the area surrounding a church of St. Peter and Paul. The research was focused on analysis of 13 children’s skull samples affected by a chronical pathology known as “cribra orbitalia” (CO). X-ray fluorescence spectrometry (XRF) and inductively coupled plasma-mass spectrometry (ICP-MS) were used to examine differences in the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Subira et al (1992) reported a lack of association between Fe concentration (by ICP–MS) and cribra orbitalia in a femur sample from Spain ( n = 197, 5th to 2nd centuries BCE). The same was observed by Grupe (1995) when measuring Fe (by AAS) in 20 orbital roofs from Germany (5th–7th centuries CE) and by Lundová et al (2023) in a Czech sample of 13 non‐adult skulls (by pXRF, 14th–16th centuries CE). Similarly, no variations in Fe concentration (by IPC–MS) were found in individuals with either cribra orbitalia, cribra humeralis, or cribra femoralis in non‐adult and adult femora from Spain ( n = 118, fifth to second centuries BCE) (García et al, 2002).…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Subira et al (1992) reported a lack of association between Fe concentration (by ICP–MS) and cribra orbitalia in a femur sample from Spain ( n = 197, 5th to 2nd centuries BCE). The same was observed by Grupe (1995) when measuring Fe (by AAS) in 20 orbital roofs from Germany (5th–7th centuries CE) and by Lundová et al (2023) in a Czech sample of 13 non‐adult skulls (by pXRF, 14th–16th centuries CE). Similarly, no variations in Fe concentration (by IPC–MS) were found in individuals with either cribra orbitalia, cribra humeralis, or cribra femoralis in non‐adult and adult femora from Spain ( n = 118, fifth to second centuries BCE) (García et al, 2002).…”
Section: Introductionsupporting
confidence: 77%
“…Sandford et al (1983) found lower Mg concentrations in individuals with cribra orbitalia, whereas neither Subira et al (1992) nor García et al (2002) observed such an association. Higher Pb content was found in the teeth ( n = 31, AAS) of non‐adult and adult individuals with cribra orbitalia from Poland (3rd to 2nd centuries BCE) (Gleń‐Haduch et al, 1997), but this trend was not recognized in other investigations (Çirak, 2016; Lundová et al, 2023; Zariņa et al, 2016). Concentrations of Ca, Mn, Cu, Zn, Sr, and Ba were also considered, yet none of these elements presented significant differences in non‐adult and adult individuals with or without cribra orbitalia (García et al, 2002; Gleń‐Haduch et al, 1997; Grupe, 1995; Sandford et al, 1983; Schutkowski & Grupe, 1997; Subira et al, 1992; Zariņa et al, 2016).…”
Section: Introductionmentioning
confidence: 90%